Geopolymerization Behaviour of Red and White Clays - Pathak, Arvind; Ranjit, Arpana; Dhakal, Bijaya (Journal of Nepal Chemical Society, 2022)
Construction is one of the most important activities increasing the demand for Portland cement resulting significant amount of CO2 emission, natural resources degradation, and a high amount of energy consumption. The use of geopolymer has been studied as a potential substitute for Portland cement. Geopolymers are environmentally-friendly binding materials that are produced by the polymerization of alumino-silicates in presence of alkali polysilicates forming Si-O-Al bonds, which are used for several building applications. In this study, red and white clays which contain solid alumino-silicate have shown reactive in presence of an alkaline activator. The addition of lime has shown improvement in the mechanical and physical properties of the geopolymer products. The FTIR analysis and SEM images of the product have shown the formation of aluminosilicate gel in the geopolymeric product. The maximum compressive strength of the geopolymer products RCW and RWL were achieved to be 15.91 and 20.30 MPa, respectively. Such geopolymer products are in good agreement with cementitious products and can be used in building applications.